Ochrona dóbr egzystencjalnych w świetle uprawnień inspekcji specjalnych (wybrane zagadnienia) - Olejniczak-Szałowska, Ewa (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The paper deals with the legal concept of obligations of the state and state administration to ensure the protection of fundamental human rights – right to life and right to health protection. The problem is analyzed on the example of the competences of selected special inspections. Such competences are of discretionary type and exhibit a high intensity of administrative power. In the case of conflict of protected interests, the legislator dictates to sacrifice the less valuable interests to cancel the threat of existential interests.
Keywords: special inspections; control of the administration; threat to life and health; freedom of economic activity